Novel L-DOPA-Derived Poly(ester amide)s: Monomers, Polymers, and the First L-DOPA-Functionalized Biobased Adhesive Tape - Manolakis, Ioannis; Noordover, Bart A. J.; Vendamme, Richard; Eevers, Walter (Macromolecular rapid communications., 2014)
The synthesis, characterization, and testing of a range of novel bio‐inspired L‐DOPA‐derived poly(ester amide)s is presented, using a widely applicable, straightforward chemistry. A model system is used to study and establish the monomer and polymer synthetic protocols, and to provide a set of optimum reaction conditions. It is further shown that fully biobased L‐DOPA‐containing adhesive tapes can be fabricated, which are positively evaluated in terms of their adhesive properties. The newly developed synthetic protocol constitutes a versatile platform for accessing and tailoring a plethora of relevant structures, including a variety of potentially biocompatible poly(ethylene glycol)‐based materials. A family of novel bio‐inspired L‐DOPA‐derived poly(ester amide)s is the subject of this work. The developed synthetic platform allows for facile synthesis, targets a wide range of structures and provides good control over the molecular and thermal properties of the resulting polymers. A particular composition containing L‐DOPA and fatty acid dimer residues is tested in terms of its adhesive performance with promising results.